Queuing system GI/M/1/N with randomly dropping packets mechanism - WANG Hao1; LI Xiao-ming1 (Tongxin xuebao)
For the original GI/M/1/N queuing system was not suitable to model the queue management mechanism,a queuing system GI/M/1/N with randomly dropping packets mechanism was discussed by means of thinning of recurrent flows.In addition,the packet loss rate,the system utility,the mean and variance of the queue length,and the average waiting time were given.